Decentralized transfer of contingency reserve: Framework and methodology. (15th November 2020) - Xiao, Jucheng; He, Guangyu; Fan, Shuai; Zhang, Siyuan; Wu, Qing; Li, Zuyi
Highlights: Elaborating realization method of decentralized transfer of contingency reserve. Instantaneous conservative response: millisecond-level and error-tolerance. Adaptive latent response: accurate frequency restoration by real-time correction. Communication-free active response considering load priority and magnitude. Conservative response capacity helps avoid adverse frequency by minimum loads. Abstract: The increasing penetration of renewable energy comes with decreasing system inertia and much faster frequency drop when contingency of large power loss occurs, which seriously threatens the security of power system operation. Meanwhile, the conventional contingency reserves will be of serious shortage and unable to satisfy security requirements in the future. To solve these problems, the concept of decentralized transfer of contingency reserve (DTCR) has been recently proposed to partially transfer the centralized contingency reserve from the supply side to the demand side, attempting to realize smart decentralized reserves with higher security and lower cost. To continue this work, this paper further elaborates the methods of implementing DTCR. Firstly, the framework of the DTCR system is formulated. Then, a refined load frequency control for contingencies is developed with millisecond-level speed and appliance-level control accuracy. The proposed three-stage control strategy is composed of instantaneous conservative response (ICR), adaptive latent response (ALR), and optimal dynamic control (ODC). As the basis of all responses, an estimation method of the range of power imbalance and frequency nadir is given, considering communication mechanism and parameter errors. In the ICR, a communication-free active response scheme is proposed considering load priority and magnitude to achieve rapid nadir control, and the setting formula of conservative response capacity (CRC) to avoid unacceptable low frequency by reliable minimum load resources is presented for the first time, which can mitigate the adverse impact caused by mis-shedding and enhance the error-tolerance. In the ALR, an online adaptive correction method is presented for key parameters to achieve accurate frequency restoration and decrease the impact of uncertainties in the sliding time window. Finally, the effectiveness of the proposed DTCR realization method is demonstrated through the simulation on a modified small-inertia IEEE 14-bus system with wind power penetration. Further tests indicate the ICR and ALR possess high security performance in the frequency control for handling contingencies.